2000
DOI: 10.1038/sj.bjp.0703624
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the human prostanoid TPα and TPβ receptor isoforms mediated through activation of the EP1 and IP receptors

Abstract: 1 The intermolecular cross-regulation mediated by the prostanoid IP-receptor (IP)/EP 1 receptor (EP 1 ) agonists PGI 2 and 17 phenyl trinor PGE 2 on TP receptor (TP) signalling within platelets was compared to that which occurs to the individual TPa and TPb receptors over-expressed in human embryonic kidney (HEK) 293 cells. Ligand mediated TP receptor activation was monitored by analysing mobilization of intracellular calcium ([Ca 2+ ] i ) following stimulation with the selective thromboxane (TX) A 2 mime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…However, the present results with the selective PKC-ε inhibitor ε-V1-2 (Lee et al, 1999) make the latter interpretation unlikely but suggest that PKC activation contributes to the TP receptor desensitization in the SHR aorta. Transfection studies on cell cultures also suggest that PKC mediates modifications of TP receptors causing their desensitization (Spurney and Coffman, 1997;Yukawa et al, 1997;Walsh and Kinsella, 2000;Yan et al, 2002;Kelley-Hickie and Kinsella, 2004). The present findings indicate that the kinase indeed contributes to TP receptor desensitization in aortae isolated from live animals and that such heterologous desensitization results from crosstalk with α1-adrenoceptors.…”
Section: Figuresupporting
confidence: 47%
See 2 more Smart Citations
“…However, the present results with the selective PKC-ε inhibitor ε-V1-2 (Lee et al, 1999) make the latter interpretation unlikely but suggest that PKC activation contributes to the TP receptor desensitization in the SHR aorta. Transfection studies on cell cultures also suggest that PKC mediates modifications of TP receptors causing their desensitization (Spurney and Coffman, 1997;Yukawa et al, 1997;Walsh and Kinsella, 2000;Yan et al, 2002;Kelley-Hickie and Kinsella, 2004). The present findings indicate that the kinase indeed contributes to TP receptor desensitization in aortae isolated from live animals and that such heterologous desensitization results from crosstalk with α1-adrenoceptors.…”
Section: Figuresupporting
confidence: 47%
“…The present results thus support the interpretation that variations in PKC isozymes underlie the desensitization of TP receptors observed in the SHR aorta. A similar conclusion was reached in TP receptor desensitization studies on cell cultures (Spurney and Coffman, 1997;Yukawa et al, 1997;Spurney, 1998;Walsh and Kinsella, 2000;Kelley-Hickie and Kinsella, 2004).…”
Section: Figurementioning
confidence: 49%
See 1 more Smart Citation
“…Both TPα and TPβ have recently been established to undergo agonist-induced homologous desensitization and phosphorylation in transfected HEK 293 cells [96]. In addition, recent studies indicate that TPβ, but not TPα, may undergo agonist-induced internalization [97,98] and we have established that the TP isoforms are subject to differential prostanoid EP 1 receptor-induced desensitization mediated at PKC sites unique to the individual TPs [63].…”
Section: Tp Receptor Desensitizationmentioning
confidence: 58%
“…Similarly, the relaxations induced by ACh via endogenous release of PGI 2 were also increased in human pulmonary veins treated with the EP 1 antagonists (AH6809, SC19220). Other studies have indicated the ability of PGI 2 to activate EP 1 -receptor in human cells (Walsh & Kinsella, 2000) or to contract guinea-pig smooth muscle via the EP 1 -receptor (Dong et al, 1986;Lawrence et al, 1992). This dual control of the venous tone via EP 1 -and/or IP-receptor in the human lung seems also present in the human hand vein (Arner & Hogesta¨tt, 1991).…”
Section: Norel Et Almentioning
confidence: 99%